The Bible in the Later Thought of F. W. J. Schelling - Geldhof, Joris (Philosophy & theology, 2004)
The author argues taht the most important source of Schelling’s ‘later thought’ is undoubtably the Bible. Schelling not only referred to it more than to any other work, he also systematically endeavored to harmonize his philosophical and theological ideas with the content of the Holy Scriptures. This was by no means evident in the post-Enlightenment context, which was characterized by its vehement critique of the Bible. The author thus investigates whether Schelling’s scripturally based forays into exegesis, dogmatic theology, and philosophy are convincing. Two Bible passages to which Schelling himself attached great weight are discussed: the prologue of St John’s gospel and the Christological hymn in St Paul’s Epistle to the Philippians. The conclusion is that Schelling’s philosophy of revelation is worth studying as an original contribution to contemporary systematic theological reflection, even if not all problems concerning the relation between biblical heritage, its possible interpretations and contemporary theological concerns are resolved.